NARRATIVE TRANSFORMATION IN THE ECRANISATION OF KAMIL KILANI’S ALI BABA AND THE 40 THIEVES - Kamilia Nur Azizah; Muhammad Nur Kholis; Rumpoko Setyo Jatmiko (Arabic Literature Department, 2024)
The development of modern filmmaking has undergone various transformations. Stories adapted into films are no longer limited to original scripts written by screenwriters but can also originate from literary works such as short stories or novels. The process of transforming written texts into films is known as ecranisation. This study examines the process of ecranisation in the short film “Ali Baba and the Forty Thieves”, an adaptation of the short story Ali Baba by Kamil Kaylani. This study aims to analyze the ecranisation process based on plot, characters, and setting elements. The theoretical framework applied in this study is Seymour Chatman’s narrative theory, focusing on plot, characters, and setting, combined with Pamusuk Eneste’s ecranisation theory, which encompasses reduction, addition, and variation in film adaptation. The data for this study were derived from the short story Ali Baba and the Forty Thieves and the short film Ali Baba, produced by the Arabian Fairy Tales YouTube channel. The findings reveal differences between the original work and the adaptation, as the resulting film does not fully reproduce the source text but represents a summary shaped by the understanding and creativity of the screenwriter and filmmaker.